2019
DOI: 10.3390/w11071322
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Kinetics of Intermediate Formation during Electrochemical Oxidation of the Organic Model Pollutant Salicylic Acid in Chloride Electrolyte

Abstract: The present study investigated the kinetics and formation of hydroxylated and chlorinated intermediates during electrochemical oxidation of salicylic acid (SA). A chloride (NaCl) and sulfate (Na2SO4) electrolyte were used, along with two different anode materials, boron doped diamond (BDD) and platinum (Pt). Bulk electrolysis of SA confirmed the formation of both hydroxylated and chlorinated intermediates. In line with the density functional theory (DFT) calculations performed in this study, 2,5- and 2,3-dihyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…2b) in the LL, whereas in the clean electrolyte BPA degradation started immediately. In clean electrolyte, active chlorine is formed at slower rates on Pt anodes than on BDD anodes [25]. The LL contains inorganic anions like Cl − and bicarbonate, which can act as hydroxyl radical scavengers.…”
Section: Removal Of Bisphenol Amentioning
confidence: 99%
“…2b) in the LL, whereas in the clean electrolyte BPA degradation started immediately. In clean electrolyte, active chlorine is formed at slower rates on Pt anodes than on BDD anodes [25]. The LL contains inorganic anions like Cl − and bicarbonate, which can act as hydroxyl radical scavengers.…”
Section: Removal Of Bisphenol Amentioning
confidence: 99%
“…The Special Issue consists of nine papers describing a wide spectrum of research related to the removal of environmentally significant pollutants from aqueous samples and their determination in various matrices. The presented articles can be classified into three broad thematic sectors related to the topic of the special issue: new methods of isolation and determination of compounds from the EOCs group [22][23][24], occurrence of EOCs in the water environment [24,25], and new approaches to the degradation of significant water pollutants or their removal [26][27][28][29][30].…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…The research conducted shows that the proposed microorganisms can be successfully used to remove platinum and palladium from contaminated waters and industrial waste. Ambauen et al [27] investigated electrochemical oxidation of the organic model pollutant salicylic acid. Two anode materials, platinum and boron doped diamond, were used along with chloride and sulfate electrolytes.…”
Section: New Approaches To Degradation Of Water Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, comparative studies in electrodes combinations were described: Yoon et al (2012) reported a flow reactor for the electrochemical degradation of phenol and 2-chlorophenol using Pt/Ti and BDD electrodes, as well as Ambauen et al (2019) comprised a electrochemical oxidation batch reactor for salicylic acid degradation with BDD and Pt electrodes. In both studies similar removal rates in the different electrodes combinations were attained, showing that not only the electrodes type highly influence the compounds degradation efficiencies, but also the physicochemical characteristics of the contaminants to be degraded.…”
Section: Introductionmentioning
confidence: 99%